2014
DOI: 10.1021/bi500587p
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Fast Kinetics of Pyroglutamate-Modified Amyloid-β Oligomers in Membrane Binding and Membrane Permeability

Abstract: Membrane permeability to ions and small molecules is believed to be a critical step in the pathology of Alzheimer’s disease (AD). Interactions of oligomers formed by amyloid-β (Aβ) peptides with the plasma cell membrane are believed to play a fundamental role in the processes leading to membrane permeability. Among the family of Aβs, pyroglutamate (pE)-modified Aβ peptides constitute the most abundant oligomeric species in the brains of AD patients. Although membrane permeability mechanisms have been studied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 94 publications
(167 reference statements)
7
48
1
1
Order By: Relevance
“…Additionally, we found that that the neuronal membrane damage caused by A␤3pE-42 results in a functional loss of plasma membrane integrity. These findings are consistent with recent publications demonstrating the capacity for A␤3pE-42 to form membrane-disrupting pores in synthetic lipid bilayers (22,23). Similarly, previous studies have shown that pE-A␤ oligomers disrupt lysosome membrane integrity in cultured neurons (50) and cause lactate dehydrogenase leakage from cultured astrocytes (49).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, we found that that the neuronal membrane damage caused by A␤3pE-42 results in a functional loss of plasma membrane integrity. These findings are consistent with recent publications demonstrating the capacity for A␤3pE-42 to form membrane-disrupting pores in synthetic lipid bilayers (22,23). Similarly, previous studies have shown that pE-A␤ oligomers disrupt lysosome membrane integrity in cultured neurons (50) and cause lactate dehydrogenase leakage from cultured astrocytes (49).…”
Section: Discussionsupporting
confidence: 92%
“…Neurons-Recent reports of pE-A␤ interactions with synthetic lipid membranes have suggested that pE-A␤ neurotoxicity is exerted via formation of ion-permeable membrane pores (22,23). We compared the capacity of A␤(1-42) and A␤3pE-42 to alter cellular ion homeostasis by measuring Ca 2ϩ flux in cortical neurons immediately following application of freshly prepared A␤.…”
Section: A␤3pe-42 Induces Rapid Ca 2ϩ Influx In Primary Corticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Since proper membrane function requires balanced structural and mechanical properties, our AFM data provide additional perspective on how polyQ aggregates might hamper cellular activity. Our observation of the enhanced bilayer rigidity by polyQ adsorption and insertion is consistent with previous AFM force measurements, which showed that larger puncture forces are required for bilayers exposed to amyloid-β prefibrillar oligomers [21, 54]. Using an AFM mode referred to as the scanning probe acceleration microscopy (SPAM), Legleiter and coworkers measured the maximum tapping force (F max ) and minimal tapping force (F min ) of lipid bilayers during each tapping event [24, 25, 49, 55].…”
Section: Discussionsupporting
confidence: 91%
“…Atomic force microscopy (AFM) and Electron microscopy (EM) have been the most frequently utilized imaging techniques for examining the structure of Aβ pores in model membranes because of their highEresolution capabilities 9,19,20 . AFM images of Aβ oligomers reconstituted in model lipid bilayers show poreElike structures with outer pore diameters of 8E12 nm 2123 . Electrical recording data obtained for various Aβ oligomers in suspended lipid membranes (also called black lipid membranes or BLM) display the heterogeneous multiple conductances characteristic of Aβ and all amyloid peptides studied to date 14,24 .…”
Section: Introductionmentioning
confidence: 99%